A terminology affair: Erythema toxicum neonatorum, or erythema transiens neonatorum? - Shelleh, H.H.; Asad, M.H. (European Journal of Pediatric Dermatology, 2000)
Since the term ETN has proved to be inappropriate etiologically and there is no evidence base of any toxicity contributing to it, it should be withdrawn and replaced by an appropriate term that contributes to this disease. We suggest the term transient erythema of the newborn or “erythema transiens neonatorum” as a substitute. We think it represents well the transient course of the disease and reflects its innocent nature.